Squatters as developers?: slum redevelopment in Mumbai - Mukhija, Vinit (England, 2003)
In the mid-1990s, the state government of Maharashtra introduced an innovative strategy of slum redevelopment in its capital city, Mumbai (Bombay). Based on demolishing existing slums and rebuilding on the same sites at a higher density, it is very distinct from the two prevalent conventional strategies with respect to slums in developing countries - slum clearance and slum upgrading. So why did the slum redevelopment strategy originate in Mumbai, and how did it do so? What were the key issues in the implementation of such a project? This critical volume responds to these questions by closely examining one particular redevelopment project over a period of twelve years: the Markandeya Cooperative Housing Society (MCHS). It analyzes the problems faced and the solutions innovated; identifies non-traditional issues often overlooked in housing improvement strategies; reveals the complexities involved in housing production for low-income groups; and combines in-depth empirical research with historical, institutional, spatial and financial perspectives to improve our understanding of complex urban development processes.
Keywords: Urban renewal-Mumbai